Comparative Analysis of PWM Techniques for Three Level Diode Clamped Voltage Source Inverter - Zulkifilie Bin Ibrahim; Md. Liton Hossain; Ismadi Bin Bugis; Jurifa Mat Lazi; Nurazlin Mohd Yaakop (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Multilevel inverters are increasingly being used in high-power medium voltage industrial drive applications due to their superior performance compared to conventional two-level inverters. Thre are a number of Pulse width modulation (PWM) techniques applied in recent years. The most widely applied PWM techniques are Sine Pulse Width Modulation (SPWM) and Space Vector Pulse Width Modulation (SVPWM).  SPWM is the most simple modulation technique that can realize easily in analog circuit.  However, it has some drawbacks such as higher total harmonic distortion (THD), lower effective DC utilization and lower switching frequency. Space vector pulse width modulation (SVPWM) is widely used because of their easier digital realization and better DC bus utilization and lower THD. The complexity is due to the difficulty in determining the reference vector location, on times calculation, and switching states selection. This paper presents a simple SVPWM algorithm for diode clamped three level inverters based on standard two-level SVPWM which can easily determine the location of reference vector, calculate the on-times, the selection of switching states. Three level diode clamped inverter (3LDCI) using space vector modulation technique has been modeled and simulated using MATLAB/SIMULINK and Origin 6.1 with a passive R-L load that can be extended to any level. Simulation results are presented to verify the proposed SVPWM control in terms of THD. The results are compared with conventional sinusoidal pulse width modulation (SPWM) where SVPWM shows better performance than SPWM in terms of THD.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6038